Solvability of a Coupled System of Fractional Differential Equations with Periodic Boundary Conditions at Resonance - Hu, Zhigang; Liu, Wenbin (Ukrains’kyi Matematychnyi Zhurnal, 2013)
By using the coincidence degree theory, we study the existence of solutions for a coupled system of fractional differential equations with periodic boundary conditions. A new result on the existence of solutions of the indicated fractional boundary-value problem is obtained.